Automobile Tire Assessment: A Multi-Criteria Approach - Ateekh-Ur-Rehman, .; Alkahtani, M. (Engineering, Technology & Applied Science Research, 2017)
In response to the present dynamic market, automobile manufacturing industries are constantly evaluating and improving their manufacturing strategies to stay competitive. It is also evident that they evaluate those strategies considering multiple criteria. In one such case, an automobile project manager has to ensure that the selected tire (among the available alternatives) complies with the prospective automobile’s performance. This paper presents an approach for the assessment of alternative automobile tires taking into account multiple criteria, such as tire sustainability, tire road performance, environmental issues, tire purchase cost and tire road grip. The presented approach is quite helpful to any decision maker who is interested not only in ranking alternatives but also in establishing the superiority of an alternative over others. The approach also helps to specify the position of each alternative with respect to ideal solution. A case illustration is used to demonstrate an application of the approach.